"ARAB SPRING" DAN PEREBUTAN PENGARUH DI SURIAH - Humphrey Wangke (Jurnal Politica, 2012)
This essay discusses waves of mass-demonstration recently in Suriah which criesfor a democratic regime change in that country. Applying the game theory, thewriter argues that the success of political reform there will be determined bythe role of external powers due to the reason that all conflicting parties haveorganized international supports. Such support will sharpen existing differentperceptions between the repressive government and democratic forces or theopposition groups. Thus, it says here that a peaceful democratic transition willbe more difficult to be reached.